Pollen-based paleoenvironmental and paleoclimatic change at Lake Ohrid (SE Europe) during the past 500 ka - Sadori, Laura; Koutsodendris, Andreas; Masi, Alessia; Bertini, Adele; Combourieu-Nebout, Nathalie; Francke, Alexander; Kouli, Katerina; Joannin, S.; Mercuri, Anna Maria; Panagiotopoulos, Konstantinos; Peyron, Odile; Torri, Paola; et al. (Biogeosciences discussions, 2015)
Abstract. Lake Ohrid is located at the border between FYROM (Former Yugoslavian Republic of Macedonia) and Albania and formed during the latest phases of Alpine orogenesis. It is the deepest, the largest and the oldest tectonic lake in Europe. To better understand the paleoclimatic and paleoenvironmental evolution of Lake Ohrid, deep drilling was carried out in 2013 within the framework of the Scientific Collaboration on Past Speciation Conditions (SCOPSCO) project that was funded by the International Continental Scientific Drilling Program (ICDP). Preliminary results indicate that lacustrine sedimentation of Lake Ohrid started between 1.2 and 1.9 Ma ago. Here we present new pollen data (selected percentage and concentration taxa/groups) of the uppermost ∼ 200 m of the 569 m long DEEP core drilled in the depocentre of Lake Ohrid. The study is the fruit of a cooperative work carried out in several European palynological laboratories. The age model of this part of the core is based on 10 tephra layers and on tuning of biogeochemical proxy data to orbital parameters. According to the age model, the studied sequence covers the last ∼ 500 000 years at a millennial-scale resolution ( ∼ 1.6 ka) and records the major vegetation and climate changes that occurred during the last 12 (13 only pro parte) marine isotope stages (MIS). Our results indicate that there is a general good correspondence between forested/non-forested periods and glacial-interglacial cycles of the marine isotope stratigraphy. The record shows a progressive change from cooler and wetter to warmer and drier interglacial conditions. This shift in temperature and moisture availability is visible also in vegetation during glacial periods. The period corresponding to MIS11 (pollen assemblage zone OD-10, 428-368 ka BP) is dominated by montane trees such as conifers. Mesophilous elements such as deciduous and semi-deciduous oaks dominate forest periods of MIS5 (PASZ OD-3, 129-70 ka BP) and MIS1 (PASZ OD-1, 14 ka BP to present). Moreover, MIS7 (PASZ OD-6, 245-190 ka) shows a very high interglacial variability, with alternating expansions of montane and mesophilous arboreal taxa. Grasslands (open vegetation formations requiring relatively humid conditions) characterize the earlier glacial phases of MIS12 (PASZ OD-12, 488-459 ka), MIS10 (corresponding to the central part of PASZ OD-10, 428-366 ka) and MIS8 (PASZ OD-7, 288-245 ka). Steppes (open vegetation formations typical of dry environments) prevail during MIS6 (OD-5 and OD-4, 190-129 ka) and during MIS4-2 (PASZ OD-2, 70-14 ka). Our palynological results support the notion that Lake Ohrid has been a refugium area for both temperate and montane trees during glacials. Closer comparisons with other long southern European and Near Eastern pollen records will be achieved through ongoing high-resolution studies.
Gesehen am 09.07.2020